2010
DOI: 10.1021/jp110709a
|View full text |Cite
|
Sign up to set email alerts
|

Reaction Pathway and Free Energy Profile for Butyrylcholinesterase-Catalyzed Hydrolysis of Acetylcholine

Abstract: Catalytic mechanism for butyrylcholineserase (BChE)-catalyzed hydrolysis of acetylcholine (ACh) has been studied by performing pseudobond first-principles quantum mechanical/molecular mechanical-free energy (QM/MM-FE) calculations on both acylation and deacylation of BChE. It has been shown that the acylation with ACh includes two reaction steps including the nucleophilic attack on the carbonyl carbon of ACh and the dissociation of choline ester. The deacylation stage includes nucleophilic attack of a water mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
48
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 41 publications
(56 citation statements)
references
References 56 publications
8
48
0
Order By: Relevance
“…These values are similar to the corresponding distances in the ES structure for BChE-catalyzed hydrolysis of ACh in our previous study. 47 This is not surprising because the only difference between ACh and ATCh is that the ester oxygen in ACh is replaced by a sulfur atom in ATCh.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These values are similar to the corresponding distances in the ES structure for BChE-catalyzed hydrolysis of ACh in our previous study. 47 This is not surprising because the only difference between ACh and ATCh is that the ester oxygen in ACh is replaced by a sulfur atom in ATCh.…”
Section: Resultsmentioning
confidence: 99%
“…40 However, a series of recent studies demonstrated that at a low substrate concentration, hydrolysis of ACh is rate-determined by the acylation reaction, 2, 41, 46 which is consistent with our recently reported study. 47 Despite extensive studies on the catalytic mechanisms of cholinesterase-catalyzed hydrolysis of ACh/ATCh, 1-2, 15, 27-30, 33-34, 36, 38, 48-50 questions remain for the mechanism of the substrate activation for BChE-catalyzed hydrolysis of ACh/ATCh. For example, what is the main factor leading to the observed substrate activation effect?…”
Section: Introductionmentioning
confidence: 99%
“…In our previous theoretical studies on cholinesterases, the oxyanion hole is always identified to stabilize the transition state and play a catalytic role in the hydrolysis reaction. 4,29,31,33 Here, we also tracked the changes of the key hydrogen-bond distances between O 1 of 6-MAM and oxyanion hole. As shown in Figure 3, the distance D1 (between the hydrogen of NH group in Gly121 and O 1 of 6-MAM) is elongated from 1.95 Å in ES a to 1.97 Å in TS1 a and then shortened to 1.90 Å in INT1 a , the distance D2 (between the hydrogen of NH group in Gly122 and O 1 of 6-MAM) is elongated from 1.79 Å in ES a to 1.86 Å in TS1 a and then shortened to 1.85 Å in INT1 a , and D3 (between the hydrogen of NH group in Ala204 and O 1 of 6-MAM) is shortened from 2.41 Å in ES a to 2.22 Å in TS1 a and then to 2.12 Å in INT1 a .…”
Section: Resultsmentioning
confidence: 99%
“…42,43 In the present study, we used the modified Gaussian03 program and modified Amber8 program which were developed in our laboratory for the purpose of performing parallel computing in both the QM and MM parts of the QM/MM calculations. 45,46,47,48 …”
Section: Methodsmentioning
confidence: 99%